Organisational Communication Occurrences: A Conceptual Dialogue - Saleh, Nor Shela; Mohd Shafie Rosli; Riki Rahman; Muhaymin Hakim Abdullah; Norizan Rameli; Nurul Aimi Razali; Yuslizar Kamaruddin (Human Sustainability Procedia, 2024)
Communication is the social interaction of two or more individuals. Communication has the potential to take place in a variety of contexts, both formally and informally. Formal communication usually occurs in work environments, whereas informal communication is interaction in everyday life. Organisational communication occurs between the top leadership and subordinates. However, it also happens among employees. The significance of organisational communication is to discuss issues, work-related goals, and the long-term goals of an organisation. The discussion needs to incorporate skilled and knowledgeable individuals to reach an all-inclusive and significant selection. Training and learning about communication development have the potential to help cultivate new skills and competencies. It is possible to develop a style of communication that is positive and allows for interaction in a positive environment. Important aspects of communication must include substance as well as contentment. This component plays a crucial role in making sure that communication is part of accurate and beneficial circumstances. As a result, organisations need to ensure that communication is vital and factual in the realm of employee and organisational wellness.